Analysis of Pig Tendencies to Stay Specific Sections Within the Pig Barn According to Environmental Parameters and Facilities Features - Dae Yeong Kang; Byeong Eun Moon; Myeong Yong Kang; Jung Hoo Kook; Nibas Chandra Deb; Niraj Tamrakar; Elanchezhian Arulmozhi; Hyeon Tae Kim (Agriculture)
Pork accounts for 34% of global meat consumption, following poultry and beef. Intensive pig farming has expanded to meet increasing demand, but space constraints and poor environmental conditions can negatively affect pig welfare. This study aimed to investigate pigs’ spatial preferences in response to environmental factors in an experimental pig barn. Six 60-day-old Yorkshire pigs were observed for 60 days. Indoor temperature (IT), relative humidity (IRH), and CO2 concentration (ICO2) were measured hourly, and pig positions were recorded using an RGB 2D-IP camera. Pearson correlation analysis was performed using SPSS. IT ranged from 14.3 °C to 25.1 °C, IRH from 78.9% to 96.5%, and ICO2 from 1038 to 1850 ppm. A strong negative correlation was found between IT and IRH (r = −0.89), while IT and ICO2 were uncorrelated (r = −0.01). Pigs showed a clear preference for sections with lower IT, supporting previous findings on thermal preference. Structural features, such as two-wall enclosures, also influenced stay frequency. These results suggest that optimizing barn structure and improving ventilation and manure management can support thermal comfort and improve welfare in intensive pig farming systems.